2002
DOI: 10.1097/00004691-200201000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Improving Lesion Conductivity Estimate by Means of EEG Source Localization Sensitivity to Model Parameter

Abstract: EEG-based source localization techniques use scalp-potential data to estimate the location of underlying neural activity. EEG source location reconstruction requires the assumption of a source model and the assumption of a conductive head model. Brain lesions can present conductivity values that are dramatically different from those of surrounding normal tissues and have to be included in head models for accurate neural source reconstruction. It is therefore necessary to analyze subjects' anatomic images (usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
0
34
1
Order By: Relevance
“…In previous studies [7], [10], where we analyzed separately the localization error due to lesion conductivity uncertainty and that due to lesion dimension estimate error, we found errors of 17 and 19 mm respectively, meanwhile in the present work those errors were reduced of about 50% (8.2 and 10.4 mm respectively). The error reduction is due to a different sampling of the scalp potentials (128 vs. 64 electrodes covering a larger scalp area).…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…In previous studies [7], [10], where we analyzed separately the localization error due to lesion conductivity uncertainty and that due to lesion dimension estimate error, we found errors of 17 and 19 mm respectively, meanwhile in the present work those errors were reduced of about 50% (8.2 and 10.4 mm respectively). The error reduction is due to a different sampling of the scalp potentials (128 vs. 64 electrodes covering a larger scalp area).…”
Section: Discussioncontrasting
confidence: 42%
“…An error on lesion conductivity assignment may lead to a location of the reconstructed source far away from the "real source". Thus, we must account for errors in lesion conductivity assignment [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the five conditions presented here on the base of the previous study [3] in which we proposed and quantified the efficacy of the reduction method (LIT) of localization errors due to LCA.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work [3] we performed a sensitivity study of the effects of lesion conductivity mispecification on the EEG dipole localization accuracy in presence of brain lesions. We found that Lesion Conductivity Assignment (LCA) errors determine source localization errors.…”
Section: Introductionmentioning
confidence: 99%